2005
DOI: 10.5194/acpd-5-9355-2005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectral light absorption by ambient aerosols influenced by biomass burning in the Amazon Basin – I. Comparison and field calibration of absorption measurement techniques

Abstract: Abstract. Spectral aerosol light absorption is an important parameter for the assessment of the radiation budget of the atmosphere. Although on-line measurement techniques for aerosol light absorption, such as the Aethalometer and the Particle Soot Absorption Photometer (PSAP), have been available for two decades, they are limited in accuracy and spectral resolution because of the need to deposit the aerosol on a filter substrate before measurement. Recently, a 7-wavelength (λ) Aethalometer became commercially… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(140 citation statements)
references
References 38 publications
5
133
0
2
Order By: Relevance
“…Two methods can be used to obtain b ap . For the first method, a nephelometer can be used to monitor aerosol scattering (b scat ) simultaneously with an aethalometer to monitor ATN; b ap can then be calculated using a correction procedure (Arnott et al 2005;Coen et al 2010;Schmid et al 2006;Weingartner et al 2003). In the second approach, b ap can be monitored directly using non-filter-based instruments.…”
Section: In Situ Light Absorption Measurements Neededmentioning
confidence: 99%
“…Two methods can be used to obtain b ap . For the first method, a nephelometer can be used to monitor aerosol scattering (b scat ) simultaneously with an aethalometer to monitor ATN; b ap can then be calculated using a correction procedure (Arnott et al 2005;Coen et al 2010;Schmid et al 2006;Weingartner et al 2003). In the second approach, b ap can be monitored directly using non-filter-based instruments.…”
Section: In Situ Light Absorption Measurements Neededmentioning
confidence: 99%
“…When absorption is stronger at shorter wavelengths, i.e., the particles appear brownish or yellow,Å will be significantly greater than unity. Values of 2.0 and more were found in aerosol collected near a lignite combustion plant (Bond et al, 1999b), in biomass smoke (Kirchstetter et al, 2004;Schmid et al, 2005;Schnaiter et al, 2005b), environmental tobacco smoke (Lawless et al, 2004), rural aerosol (Lindberg et al, 1993), and in particles produced by oxygen-deficient combustion of propane (Schnaiter et al, 2006). The highest values ofÅ are found for the yellowish to brownish products of pure smoldering combustion, e.g., tobacco smoke (3.5, Lawless et al, 2004) or water-soluble HULIS from biomass burning (6-7, Hoffer et al, 2005).…”
Section: Wavelength Dependence Of Absorption and Its Possible Effect mentioning
confidence: 99%
“…The absorption cross section of C brown increases very sharply with decreasing wavelength, with a slope of λ −2 to λ −6 , whereas C soot (e.g., from diesel vehicles) shows a λ −1 dependence (Kirchstetter et al, 2004;Hoffer et al, 2005;Schmid et al, 2005) (see also Sect. 3).…”
Section: Thermochemical Analysis ("Ec")mentioning
confidence: 99%
“…Hansen et al (1984) developed a continuous integrating plate monitor using optically thick quartz fiber filters, and instrument vendors have since produced a variety of user-ready monitors derived from this and other integrating plate designs. A great deal of work has been done to characterize and reconcile the responses of such instruments to realistic aerosols, both in the lab (Gerber and Hindman 1982;Clarke et al 1987;Hitzenberger 1993;Horvath 1993;Bond et al 1999;Weingartner et al 2003;Sheridan et al 2005;Muller et al 2011) and through comparisons in the field (Liousse et al 1993;Reid et al 1998;Schmid et al 2006;Chow et al 2009;Collaud Coen et al 2010). These studies have identified sources of measurement bias that can be loosely grouped into three categories requiring different forms of correction: filter effects, loading dependence, and particle scattering interference.…”
mentioning
confidence: 99%